Desentralisasi dan Tantangan Otonomi Daerah: Analisis Kebijakan dengan Pendekatan Mixed-Method - Hasanah, Nur; Syah, Erwin (Universitas Sains dan Teknologi Komputer, 2025)
Decentralization has been implemented in Indonesia as a strategy to enhance regional governance and foster local development. However, despite its potential benefits, decentralization faces significant challenges, including fiscal disparities, administrative inefficiencies, and corruption at the regional level. Unequal revenue distribution among regions has resulted in dependency on central government transfers, while limited administrative capacity has hindered effective policy implementation. This study aims to evaluate the effectiveness of decentralization policies in Indonesia using a mixed-method approach that combines quantitative analysis of financial reports and regional governance indicators with qualitative insights from interviews with policymakers and public administration experts. The findings reveal that regional budget realization improved from 68% in 2018 to 72% in 2023, while the Regional Governance Performance Index (IPKD) increased from 60% to 70% during the same period. However, fiscal dependency remains a major issue, with 80% of regional revenues still relying on central government transfers. Additionally, corruption cases involving local officials increased from 110 in 2018 to 160 in 2023, highlighting governance weaknesses and the lack of transparency. These findings indicate that decentralization in Indonesia has yet to fully achieve its objectives due to structural and institutional challenges. This study contributes to the ongoing discourse on decentralization by identifying key constraints and proposing policy recommendations, including strengthening fiscal autonomy, enhancing transparency through digital governance, and improving administrative capacity. A more structured, transparent, and accountable decentralization framework is essential to ensure sustainable and equitable regional development in Indonesia.